Antibacterial effect of an extract of the endophytic fungus Alternaria alternata and its cytotoxic activity on MCF-7 and MDA MB-231 tumour cell lines - EZHIL ARIVUDAINAMBI, U.S.; KANUGULA, ANANTHA KOTESWARARAO; KOTAMRAJU, SRIGIRIDHAR; KARUNAKARAN, CHANDRAN; RAJENDRAN, AYYAPPAN (Biological Letters, 2015)
There is a growing need for new and effective antimicrobial agents to treat life-threatening diseases. Fungal endophytes are receiving increasing attention by natural product chemists due to the diverse and structurally unprecedented compounds, which make them interesting candidates for drug discovery. The present study evaluates the antibacterial activity of ethyl acetate extract of the endophytic fungus Alternaria alternata VN3 on multi-resistant clinical strains of Staphylococcus aureus and Pseudomonas aeruginosa, as well as its cytotoxicity on MCF-7 and MDA MB-231 tumour cell lines of breast cancer. The maximum inhibition zone of 21.4±0.07 mm and 21.5±0.25 mm was observed for S. aureus strain 10 and P. aeruginosa strain 2, respectively. The ethyl acetate extract showed minimal inhibitory concentration ranging from 100 to 900 μg/ml for S. aureus and P. aeruginosa. Further, the ethyl acetate extract of A. alternata VN3 exhibited moderate anticancer activity against MCF-7 and MDA MB-231 cell lines. At 30 μg/ml the cell viability was decreased to 75.5% and 71.8% for MCF-7 and MDA MB-231 cells, respectively. These results clearly indicate that the metabolites of A. alternata VN3 are a potential source for production of new drugs.